Juridical Implications of the Distribution of Congenital Children's Inheritance Based on KHI (Study of Court Decision No. 449/Pdt.G/2024/Pa. Twg) - Hafid Ansori; Iwannudin Iwannudin; Agus Setiawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the judge's considerations in determining the inheritance rights of congenital children and examine the arrangement and legal position in the inheritance distribution system according to the Compilation of Islamic Law in the Decision of the Religious Court Number 449/Pdt.G/2024/PA.Twg. This research is an empirical normative legal research with a statutory approach and a case approach, using secondary data in the form of court decisions, provisions of the Compilation of Islamic Law, and supported by research instruments in the form of interview guidelines and documentation to examine the construction of judges' legal considerations. The analysis was carried out qualitatively through a systematic interpretation of the norms of Islamic inheritance and its relevance to the legal facts revealed in the trial. The results of the study show that the judge bases his consideration on the principle of the relationship of nasab as the main basis of inheritance, normative provisions in the Compilation of Islamic Law, and the principle of justice and legal certainty in dispute resolution. A congenital child juridically only has an inheritance relationship with his or her biological parents and does not have a position as an heir of the stepparent because there is no legal blood relationship according to Islamic law. The regulations in the Compilation of Islamic Law provide strict restrictions on the subject of heirs so as to ensure legal certainty in the distribution of inheritance. This study emphasizes the importance of consistency in the application of Islamic inheritance norms in order to prevent the expansion of interpretations that can cause legal uncertainty in the practice of religious justice.